2016
DOI: 10.1371/journal.pone.0148477
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Affects Hemocyte Physiology in the Tanner Crab (Chionoecetes bairdi)

Abstract: We used flow cytometry to determine if there would be a difference in hematology, selected immune functions, and hemocyte pH (pHi), under two different, future ocean acidification scenarios (pH = 7.50, 7.80) compared to current conditions (pH = 8.09) for Chionoecetes bairdi, Tanner crab. Hemocytes were analyzed after adult Tanner crabs were held for two years under continuous exposure to acidified ocean water. Total counts of hemocytes did not vary among control and experimental treatments; however, there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 108 publications
0
33
0
Order By: Relevance
“…Fisher et al (2000) found a reduced concentration of hemocytes in the oyster Crassostrea virginica under long-term stress of petroleum hydrocarbon. Meseck et al (2016) indicated that ocean acidification also resulted in decreased THC of the crab Chionoecetes bairdi. Similarly, in the present study, THC decreased with nano-TiO 2 concentration increase and pH decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Fisher et al (2000) found a reduced concentration of hemocytes in the oyster Crassostrea virginica under long-term stress of petroleum hydrocarbon. Meseck et al (2016) indicated that ocean acidification also resulted in decreased THC of the crab Chionoecetes bairdi. Similarly, in the present study, THC decreased with nano-TiO 2 concentration increase and pH decrease.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis is that reduced seawater pH led to differences in intracellular pH, which could alter the ability of cells to participate in the mineralization process. In another crustacean (the Tanner crab, Chionoecetes bairdi), a reduction in intracellular pH was observed in animals held at reduced pH, a response that was proposed to have implications on the shell formation process (Meseck et al, 2016). Direct assessments of intracellular pH in barnacles grown at reduced pH as well as further investigation into the role of cells in the shell formation process in barnacles would be helpful in evaluating these mechanisms.…”
Section: Shell Formationmentioning
confidence: 99%
“…Studies of physiological responses of crabs exposed to elevated pCO 2 ( Pane and Barry, 2007 ; Spicer et al, 2007 ; Fehsenfeld et al, 2011 ) have identified a wide range of responses ( Kroeker et al, 2010 ). High CO 2 has been reported to negatively impact various physiological processes, including growth ( Walther et al, 2010 ), survival ( Melzner et al, 2009 ), development ( Walther et al, 2010 ; Schiffer et al, 2013 ), immune response ( Meseck et al, 2016 ), chemoreception ( de la Haye et al, 2012 ), and swimming performance ( Dissanayake and Ishimatsu, 2011 ). The most immediate physiological responses to ocean acidification (OA) in marine crustaceans are best described by acid–base adjustments ( Pane and Barry, 2007 ; Pörtner et al, 2010 ; Whiteley, 2011 ).…”
Section: Introductionmentioning
confidence: 99%